Empirical evaluation of Soil Conservation Service Curve Number inspired sediment yield model - LAL, MOHAN; MISHRA, S. K.; PANDEY, ASHISH (Journal of Soil and Water Conservation, 2017)
The present study was carried out to evaluate the performance of Soil Conservation Service curve number (SCS-CN) based sediment yield model which was developed by coupling the SCS-CN method with the universal soil loss equation (USLE) to predict the sediment yield from a given rainfall event. The eleven natural rainfall (P), runoff (Q) and sediment (Y) events observed from twelve experimental plots of size 22 m Ã— 5 m each having different land uses (Sugarcane, Blackgram, Maize and Fallow land), slope (5, 3, and 1%) and soil infiltration capacity located in Roorkee, Uttarakhand, India were utilized for validating the model to decide its applicability to predict event wise sediment yield in study region. The resulting efficiencies obtained from model calibration and validation phase indicate the satisfactory performance of the model for applying it in study region for sediment prediction. The existence of good correlations between the curve numbers (CN) derived from original SCS-CN method and the sediment yield model supported the analytical approach of coupling of the SCS-CN method with USLE. The initial abstraction ratio (Î») was also found to play an important role in sediment prediction because the efficiency of prediction was found to improve from 65.92 to 66.83 as Î» was decreased from 0.25 to 0.05, respectively. Thus, results from present study support the application of SCS coupled sediment model for predicting the event based sediment yield.